Colon leiomyosarcoma - Da Silva, Emma; Bounous, Mario (Cirugía del Uruguay, 1993)
A case of leiomyosarcoma of descending colon is presented; this is possibly the first one of this type in national literature. Based on an extensive bibliographical revision, considerations are made on different diagnostic and therapeutical problems.